The Influence of Entrepreneurship Education, Entrepreneurial Self-Efficacy and Family Environment on Higher Education Students' Entrepreneurial Interest: Empirical Evidence on Students in Universitas Pendidikan Indonesia - Yori Andes Saputra; Dinn Wahyudin; Fitri Novilia (West Science Social and Humanities Studies, 2024)
The research's objective is to investigate and assess the impact of entrepreneurship education, entrepreneurial self-efficacy, and Family Environment on the entrepreneurial interest of students at Universitas Pendidikan Indonesia. This study employs a quantitative research design, with 96 samples selected for each research object through quota sampling, resulting in a total sample size of 96. The method involves lemeshow sampling, and data collection is conducted through accidental sampling. The analysis method utilized is multiple linear regression. The findings reveal that entrepreneurship education, entrepreneurial self-efficacy, and environmental factors collectively influence entrepreneurial interest among the students.